THE PRESENCE OF AUTOCORRELATION ON THE T-2 CONTROL CHART OF HAROLD HOTELLING - Leoni, Roberto Campos [UNESP]; Branco Costa, Antonio Fernando [UNESP]; Guerreiro Machado, Marcela Aparecida [UNESP] (Univ Federal Fluminense, Escola Engenharia, Dept Engenharia Producao, 2017)
The presence of autocorrelation violates the hypothesis of data independence used in statistical control charts in the manufacturing environment. This article examines graphically, using the Mahalanobis distance, the effect of autocorrelation in two measurable quality characteristics of X and Y, whose correlation and autocorrelation structures are from a VAR model(1). With the graphical evaluation, it is possible to understand that the presence of autocorrelation cannot be neglected by the users who use as statistical tool the control charts to monitor processes.
Keywords: Autocorrelation; Control Chart; T-2 of Hotelling